2022
DOI: 10.3390/microorganisms10050936
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacillus licheniformis and Bacillus subtilis on Gut Barrier Function, Proinflammatory Response, ROS Production and Pathogen Inhibition Properties in IPEC-J2—Escherichia coli/Salmonella Typhimurium Co-Culture

Abstract: The emergence of antimicrobial resistance raises serious concerns worldwide. Probiotics offer a promising alternative to enhance growth promotion in farm animals; however, their mode of action still needs to be elucidated. The IPEC-J2 cell line (porcine intestinal epithelial cells) is an appropriate tool to study the effect of probiotics on intestinal epithelial cells. In our experiments, IPEC-J2 cells were challenged by two gastrointestinal (GI) infection causing agents, Escherichia coli (E. coli) or Salmonel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that B. subtilis can directly enhance the immunity of animals by increasing serum immunoglobulin levels [ 69 ] and the expression of immune-related genes [ 70 ]. Meanwhile, B. subtilis also indirectly enhances the immunocompetence by maintaining the intestinal epithelial integrity, downregulating the secretion of inflammatory factors, inhibiting pathogenic bacterial adhesion, and stimulating the growth of immune cells [ 71 , 72 ]. In terms of B. subtilis species, the RBS group obtained remarkably high activities of LZM, ACP, and AKP as well as a high transcription of propo , but low transcriptions of of tlrs, litaf , and relish compared with the unmodified one.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that B. subtilis can directly enhance the immunity of animals by increasing serum immunoglobulin levels [ 69 ] and the expression of immune-related genes [ 70 ]. Meanwhile, B. subtilis also indirectly enhances the immunocompetence by maintaining the intestinal epithelial integrity, downregulating the secretion of inflammatory factors, inhibiting pathogenic bacterial adhesion, and stimulating the growth of immune cells [ 71 , 72 ]. In terms of B. subtilis species, the RBS group obtained remarkably high activities of LZM, ACP, and AKP as well as a high transcription of propo , but low transcriptions of of tlrs, litaf , and relish compared with the unmodified one.…”
Section: Discussionmentioning
confidence: 99%
“…The two cell lines used in this study are also suitable for measuring oxidative stress levels since they are both exposed to high levels of reactive oxygen species (ROS) under physiological conditions. Issues arise when the ROS exceeds antioxidant capacity, called oxidative stress, and processes such as lipid peroxidation or protein damage occur, ultimately leading to cell death [48,49]. The IPEC-J2 experiment revealed a significant elevation in H 2 O 2 levels when S. suis was used alone and when bacterial exposure was combined with MI-471.…”
Section: Discussionmentioning
confidence: 99%
“…Adding Bacillus licheniformis to diet amplified mRNA expression of NF-κB in the jejunum of broilers and in turn activation of their signaling cascade leading to initiation of cellular responses of innate immune cells and production of proinflammatory cytokines [82]. Porcine intestinal epithelial cells (IPEC-J2 cells) treated with Bacillus licheniformis showed increased production of the proinflammatory cytokine, IL-8, significantly more than the control group, while Bacillus subtilis increased IL-6 secretion [83]. This indicate that normal microbiota might increase proinflammatory cytokines similar to pathogen induced response as detected in other studies [84].…”
Section: Discussionmentioning
confidence: 99%